Origin and chemistry of petroleum : proceedings of the Third Annual Karcher Symposium, Oklahoma, May 4, 1979 - Atkinson, Gordon; Zuckerman, Jerry J. (Pergamon Press, 1981)
Origin and Chemistry of Petroleum explains that petroleum is produced from exceptionally disseminated organic matter of biological origin encased in extremely buried sediments. Production of petroleum starts when such sediments are exposed to higher temperatures resulting from increased depths of entombment in the sedimentary column. The book discusses that once the petroleum is created from source rocks, the material transfers into porous reservoir rocks. Such rocks, when discovered, will give enough supply of petroleum for commercial production. An evaluation of the molecular analysis of the.